Study on the Influence of Rock Shape on Rolling Distance - Feng Liu; Ning Hu; Gangchen Sun; Bai Yang (Applied Sciences, 2023)
To explore the influence of rock shape on rolling distance and effectively mitigate rockfall hazards, the following research was conducted. Factors influencing the rolling distance of rocks were determined through model experiments, and the mechanics of rolling resistance were analyzed. The coefficient RF, reflecting the ease of rock rolling, and the shape parameter ψ, quantifying the rolling distance, were proposed. By incorporating the shape parameter into kinematic equations, formulas for calculating the rolling distance of rocks with varying shapes on diverse ground characteristics were derived. These formulas underwent validation using data from model experiments, revealing minimal disparities between the experimental and calculated values. Irregularities on the rolling surface, commonly referred to as “steps” due to the differences in surface hardness among various materials, as well as deviations and shifts in the rolling axis during rock movement, were identified as the primary factors influencing rolling distance and contributing to calculation errors. Combining these deviations for rocks of distinct shapes with theoretical formulas enabled the determination of the range of influence of rock rolling at various velocities, offering valuable insights for assessing areas prone to rockfall hazards.